Last resort. The complete series [videorecording (DVD)] - Braugher, Andre; Speedman, Scott; Betts, Daisy (Sony Pictures Home Entertainment, 2013)
After Navy SEALs are picked up in a US submarine, they receive orders to launch a nuke. The Captain refuses to fire, even though he was ordered to do so. The US sub is then attacked. When they escape the attack, the crew and the Navy SEALs find a small island to take refuge on.